Subcutaneous foslevodopa/foscarbidopa initiation in a Parkinson’s day-clinic - a suitable setting to ensure treatment efficacy, tolerability and psychosocial adaption - Jander, Alina; Bergner, Sarah; Schönwald, Beate; Pötter-Nerger, Monika; Buhmann, Carsten; Hidding, Ute (Frontiers in Aging Neuroscience, 2025)
BackgroundSubcutaneous foslevodopa/foscarbidopa (LDp/CDp) has expanded the treatment options in advanced Parkinson’s disease (aPD). However, the most appropriate therapeutic setting for therapy implementation is not clear.ObjectiveTo present a concept for LDp/CDp therapy implementation in a Parkinson’s day-clinic and efficacy and safety outcome data from patients under the new therapeutic regimen.MethodsRetrospective clinical data were collected from the first 24 patients with aPD who were initiated on LDp/CDp treatment at the Hamburg Parkinson’s day-clinic. Outcome parameters were analyzed in terms of motor symptoms (MDS -UPDRS II-IV), safety aspects and effects on patients’ quality of life (PDQ-39).ResultsThe concept of the Parkinson’s Day-clinic enabled the successful implementation of LDp/CDp therapy in patients with advanced Parkinson’s disease (aPD). It provided individualized medical supported via neurologists, specialized nurses and therapists and thus facilitated the transition from clinic-based care to home-based support. Compared to previous optimized oral treatment, the application of LDp/CDp significantly reduced motor complications such as dyskinesias and motor fluctuations by 53% on the MDS-UPDRS IV (p = 0.0094). Motor function improvements were paralleled by a numerical increase in activities of daily living scores (MDS-UPDRS II) and improvement in long-term mobility (PDQ-39 mobility subscale), suggesting potential benefits in daily functioning and perceived mobility.ConclusionThe value of our data is limited by its retrospective design and small sample size. However, the data suggest that a proper day-clinic setting enables the successful implementation of subcutaneous LDp/CDp therapy with improvement of motor functions and reduction of side effects. It also ensures the necessary intensive medical support and offers comprehensive device-related and psychosocial guidance for both patients and caregivers.